Research on Setting Parameters of Generator Excitation System with Low Excitation Limit based on Heffron-Philips - Qian Huang, Nina Dai, Pengdan Ge, Lihong Xiang, Qingshan Xu, Guoping Lei (Forest Chemicals Review)
In order to improve the reliability and stability of large electric generator, Based on the analysis of the Heffron-Philips mathematical model of generator excitation system, The article studied the theoretical method of parameter setting under different working conditions of low excitation limit link, constructed the single-machine infinite-bus system simulation model with excitation controller using PSCAD/EMTDC simulation software, The results of theoretical analysis of excitation system are verified. The variable low excitation limit parameters are simulated under different working conditions, Compared the dynamic response curves of excitation system regulated by different low excitation limiter, It provides a basis for the design and selection of low excitation limit of excitation system.